THE SOCIALIZATION OF CLASSROOM ACTION RESEARCH FOR THE TEACHERS OF BERINGIN BANGUN PURBA VACATIONAL SCHOOL IN PANDEMIC SITUATION - Tampubolon, Sahlan; Sinaga*, Nenni Triana; Lumbantoruan, Febrika Dwi Lestari (Jurnal Abdimas Mutiara, 2021)
Various polices carried out by the government to improve the education, especially during this pandemic. The pandemic has a negative impact on the society, especially in the education field. Evaluation of the teaching process is very important to do in the currents situation. Classroom action research is the good solution to solve those problems. There are four main concept on classroom action research, namely: planning, action, observation, and reflection. The teachers can evaluate the class by implementing those concept. The implementation also do in each subject of the teacher’s class. Teacher may do it while they teaches their students in the learning process. By this socialization, teacher can evaluate their class in their daily activities at school. Classroom action research gives the positive impact to the teachers and also as a researchers.